Development and validation of students' attitude to economics scale using item response theory (2020)
As important as attitude scales are in the teaching and learning domain, scales on affective traits are relatively limited especially those developed by using IRT based models. This study developed and validated an instrument-the Students Attitude to Economics Scale (SATES), using the IRT model. At the initial exploratory stage, data obtained from a sample of973 high school economics students were subjected to parallel and full information item factor analyses with multidimensional graded response model. This was based on the number of dimensions identified under parallel analysis to identify the interpretable factors underlying the scale. A total of 14 items of the initial 55 constructed items emerged with four factors named; difficulty of economics, performance in economics, benefits of economics and pedagogy of economics. To assess the construct validity of the SATES, the differential functioning of the items on the scale, with respect to the sex of the respondents, were assessed. The results showed that all the 14 items had insignificant chi-square value (p > 0.05). Meaning that all the 14 items that survived item analysis functioned similarly among males and females, hence were valid items. To estimate the reliability of the 14-item SATES, the responses of the testees to the 14 items were subjected to empirical reliability analysis, an IRT based reliability estimate. The outcome revealed a reliability estimate of 0.75, 0.73, 0.84, and 0.79 for each of the four factors respectively, hence 0.78 for the SATES. To cross-validate the 14-item SATES, it was administered to another sample of 1,274 high school economics students, and the invariance of the scale was assessed. To achieve this, response was subjected to multiple group multidimensional item response theory analyses. This provided evidence of the construct validity of the instrument, indicating that the instrument is a valid and reliable tool for measuring senior secondary school students' attitude towards economics.